Flaunting dissonance: The queering of narrative and gender boundaries in Patrick White's The Aunt's Story. (June 2023) - Graham-Smith, Greg
The Twyborn Affair (1979) is generally regarded as Patrick White's covert "coming out" novel, followed by his frank "confession" in his autobiography, Flaws in the Glass (1981). However, this article explores how even an earlier work such as The Aunt's Story (1977/1948), from the Nobel laureate's modernist phase, may be seen as a pre-text for the gay self, whereby the author stages incomplete representations of his own subaltern position in the characters he "becomes" in his writing. Through a series of textual feints, his persona is disseminated in the form of polyvalent alternative selves which belie any possibility for recuperation of a stable, authentic selfhood. White thereby refuses the univocal inscription of subjectivity upon which sexual hegemony is predicated. What I aim to do in this article is to extend the particularities of the novel's writing strategies (found in the Jardin Exotique section, for example, which functions as a Foucauldian heterotopic space) into the province of gender. In doing so, I will show how the gay author, through the central character, Theodora Goodman's protean identities and the deployment of competing narrative epistemologies, can fabricate alternative subject positions. These attest not only to the artificial technologies of gender constitution, but also function as remnants of White's own divided status, brought about by his dissonant subaltern position in the borderlands of representation.